The prevalence of low back pain and its relationship with physical activity, age and BMI in Fars Payam-e Noor University staff - Abdolhamid Daneshjoo; Hossein Dadgar (مجله پژوهش در علوم توانبخشی, 2011)
Introduction: The purpose of this study was to determine the prevalence of low back pain and to evaluate its relationship with physical activity, age and BMI in Fars Payam-e noor University (PNU) staff. Materials and Methods: Of the total number of 709 Fars PNU employees, 182 men and women working in 12 branches of this university across Fars Province-Iran were chosen objectively. Low back pain data were collected via Quebec questionnaire. Chi-square test, Pearson correlation coefficient and ANOVA test were used for statistical analysis of data (significance level set at P < 0.05). Results: The study results showed a high prevalence of low back pain (86/3%) among studied sample, especially in the age range of 30 to 40 years. There was a significant difference between people with LBP and those without LBP (P = 0.000), but no significant difference between faculty members and university staff was observed (P > 0.05). Low back pain was negatively related to physical activity (P = 0.02). Moreover, there was no significant correlation between LBP and either age or sex (P > 0.05). Most subjects had normal body mass indexes (BMI). In addition, statistical analysis of data through ANOVA indicated a significant relationship between BMI and low back pain (P = 0.02). Conclusion: The Results indicate that employees who had regular physical activity have less low back pain. Given positive relation between regular activity and less low back pain we recommend that employees allocate some time for regular physical activity in their weekly schedule in order to prevent low back pain. Keywords: Low back pain, University staff, Regular activity